(untitled) (PANGEEA, 2025)
Urban transportation and mobility in Cluj-Napoca are characterized by a heterogeneous and asymmetric infrastructure and dynamics due to the specific location and topology of a riverside locality. This analysis delves into urban mobility issues through the lenses of infrastructure and road dynamics, encompassing interurban passenger transportation, limited geographically and polarized by the existing network, and the analysis of regular air traffic from Cluj-Napoca’s Avram Iancu Airport and its implications. The results and conclusions shed light on the reasons behind the upheavals witnessed in the last 15 years concerning urban mobility flows, influenced by transportation dynamics across all levels, commuter patterns, urban and peri-urban transit. Furthermore, original analyses are presented, diverging from existing mobility studies.